Videogame and healthy living: stress or collaboration? - Fensterseifer, Alex (2012)
The review refers to a critical analysis about themaster’s thesis conductedby Mateus David Finco, entitled “Wii Fit: the game a healthy lifestyle”, defendedat theGraduate Program in Human Movement Sciences, Federal University of Rio Grandedo Sul, in 2010. The paper discusses the relationships /effects between video games andlifestyle of its users.